Mini DNA-barcode as molecular marker for heavily processed hairtail fish products authentication. (May 2019) - Abdullah, A; Nurilmala, M; Jacoeb, A M; Sitaresmi, K P
Abstract: Fish species mislabeling, wrongful description, and substitution by species with a lower value are problems that occur due to globalization of fish markets. Establishment of fishery products and seafood species identification methods becomes an important task for Indonesian fishery research laboratories and seafood control authorities. Therefore, various DNA barcode markers must be tested to determine which markers are suitable for rapid, simple, and applicable methods. This study aimed to determine the reliability of full-length DNA barcode and mini DNA-barcodes for raw fillets and numerous cooked Indonesian hairtails. The results showed all DNA barcode markers were successfully applied to all of the samples with the species level assignment of 97-100%. Our study proposed a practical molecular marker for the monitoring of quality and food safety assurance of important hairtail products.